Bentuk-bentuk Pemulihan Akhlak bagi Pesalah Seks di Malaysia: Suatu Sorotan Literatur: Classifications of Moral Rehabilitation for Sex Offenders in Malaysia: A Literature Review - Ibrahim, Nursyahidah; Mansor, Nurul Husna; Md Yusoff, Yusmini (Jurnal Usuluddin, 2020)
Sexual misconduct is not a new occurrence in Malaysia. It is a global issue that has raised concern and threatened the well-being of a society. From here, a recovery intervention program was introduced to help those who are involved with anti-social behaviour in order to restore their physical and spiritual welfares. The existence of rehabilitation institutions and correctional centres in Malaysia plays a significant role as it acts as platforms in implementing moral rehabilitation programs by formulating various modules and activities. In summary, there are two forms of moral rehabilitation which are institutional rehabilitation and communal rehabilitation. Hence, this paper will identify the types of moral rehabilitation meant for sex offenders at rehabilitation institutions and correctional centres in Malaysia. This paper applies the qualitative approach through descriptive analysis method based on findings from previous studies. Based on theses findings, it is found that there are generally four types of moral rehabilitation in rehabilitation institutions and correctional centres which are religious/spiritual rehabilitation, rehabilitation based on Islamic guidance and counselling, rehabilitation based on vocational training and education and rehabilitation based on social and physical development.